2016
DOI: 10.1007/s12010-016-2038-3
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of the Production of Inactivated Clostridium novyi Type B Vaccine Using Computational Intelligence Techniques

Abstract: Clostridium novyi causes necrotic hepatitis in sheep and cattle, as well as gas gangrene. The microorganism is strictly anaerobic, fastidious, and difficult to cultivate in industrial scale. C. novyi type B produces alpha and beta toxins, with the alpha toxin being linked to the presence of specific bacteriophages. The main strategy to combat diseases caused by C. novyi is vaccination, employing vaccines produced with toxoids or with toxoids and bacterins. In order to identify culture medium components and con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…TcnA is encoded within a prophage genome in both C. novyi toxinotypes [257]. This bacteriophage is believed to regulate toxin production and morphology [258,259,260]. Moreover, homologous genes or a novel C. perfringens toxin regulator (CPE1446-CPE1447) [261] and an AgrD quorum sensing peptide (Cno-19402) [7] are found in C. novyi.…”
Section: Clostridium Novyimentioning
confidence: 99%
See 1 more Smart Citation
“…TcnA is encoded within a prophage genome in both C. novyi toxinotypes [257]. This bacteriophage is believed to regulate toxin production and morphology [258,259,260]. Moreover, homologous genes or a novel C. perfringens toxin regulator (CPE1446-CPE1447) [261] and an AgrD quorum sensing peptide (Cno-19402) [7] are found in C. novyi.…”
Section: Clostridium Novyimentioning
confidence: 99%
“…C. novyi is grown for 18 to 72 h at 37 °C and inactivation of TcnA is achieved by incubation with 0.4% formalin at 37 °C for three days [227]. A more recent study showed that modeling the difficult C. novyi fermentation process using computational tools allowed optimization of toxin productivity, cell density, and fermentation time [260].…”
Section: Clostridium Novyimentioning
confidence: 99%
“…1) In cattle the way to prevent this disease is vaccination, employing vaccines produced with toxoids or with toxoids and bacterins [17,[130][131][132].…”
Section: Novyi Toxinsmentioning
confidence: 99%
“…The standardization of culture in industrial reactors is complex, since the release of toxin into the medium is quite erratic between batches, starting and reaching its peak at different times [130,133]. At present, toxin concentration is measured by using in vivo methods by means of experimental animals, which have clear drawbacks.…”
Section: Novyi Toxinsmentioning
confidence: 99%
“…the data acquisition analysis for multiple sensors using modulation frequency with telemetry technique can be done. [5]In addition, ANFIS is also widely used in various researches, such as the use of ANFIS for the stability of single machine power output [6] and multi engine [7], broiler cage temperature setting [8], color clashing on ancient inscriptions [9], for Short-Term Load Forecasting [10], Evaluation of Flashover Voltage Levels of Contaminated Hydrophobic Polymer Insulators [11], for determination of PH value [12], to detect breast cancer [13], determination of river flow direction [14], Optimization of the Production of Inactivated Clostridium novyi Type B Vaccine [15], Quantitative Structure-Activity Relationship Model for HCVNS5B inhibitors based on an Antlion [16] determination of forecasting volcanic eruption [17], density prediction for long term wind power [18], prediction water quality index of Satluj river in India [19]. To predict the seismic strength level cannot be predicted certainty by stochastic method.…”
Section: Introductionmentioning
confidence: 99%